2015
DOI: 10.1111/jeu.12262
|View full text |Cite
|
Sign up to set email alerts
|

Fast Technology Analysis Enables Identification of Species and Genotypes of Latent Microsporidia Infections in Healthy Native Cameroonians

Abstract: Several enteric microsporidia species have been detected in humans and other vertebrates and their identifications at the genotype level are currently being elucidated. As advanced methods, reagents, and disposal kits for detecting and identifying pathogens become commercially available, it is important to test them in settings other than in laboratories with “state-of-the-art” equipment and well-trained staff members. In the present study, we sought to detect microsporidia DNA preserved and extracted from FTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…isolated in various animal hosts and water samples (2). Genotypes KIN-1, CHN4, and Henan-III have only been discovered in a few human cases of microsporidiosis, with genotype KIN-1 in a Cameroonian, while genotypes CHN4 and Henan-III in three and one Chinese, respectively (18)(19)(20). Additionally, they have also been found in some animals from China.…”
Section: Discussionmentioning
confidence: 99%
“…isolated in various animal hosts and water samples (2). Genotypes KIN-1, CHN4, and Henan-III have only been discovered in a few human cases of microsporidiosis, with genotype KIN-1 in a Cameroonian, while genotypes CHN4 and Henan-III in three and one Chinese, respectively (18)(19)(20). Additionally, they have also been found in some animals from China.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocompromised individuals were believed to be more vulnerable to microsporidia infections ( 5 ). However, accumulating evidence showed that immunocompetent individuals would also be infected, and the outcomes are often asymptomatic and therefore lead to latent infections ( 6 , 7 , 8 ). For instance, one study conducted in Cameroon revealed that 87% of teenagers and 68% of healthy asymptomatic individuals actually had subclinical microsporidia infections and were shedding spores ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings revealed the incidences of latent infection and persistence of microsporidia in immunocompetent individuals are much higher than we used to think. Although the issues about the latent infection of microsporidia in immunocompetent individuals had long been underestimated, it should now be paid more attention because the wide existence of microsporidia in nature and the wide host ranges of them may lead to emerging infections and serious public health problems ( 8 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immune-compromised individuals were believed to be more vulnerable to microsporidia infections (5). However, accumulating evidence showed that immune-competent individuals would also be infected, and the outcomes are often asymptomatic and cause latent infections (6)(7)(8). For instances, one study conducted in Cameroon revealed that 87% teenagers and 68% healthy asymptomatic individuals were actually had subclinical microsporidial infections and were shedding spores (9).…”
Section: Introductionmentioning
confidence: 99%
“…These findings revealed the latent infection and persistence of microsporidia in immune-competent individuals are much higher than we used to think. Although the issues about the latent infection of microsporidia in immune-competent individuals had long been under-estimated, it should now be paid more attentions since the wide existence of microsporidia in nature and the wide host ranges of them may lead to emerging infections and serious public health problems (8, 12).…”
Section: Introductionmentioning
confidence: 99%